The Effect Of Boiler Type, Unit Capacity, And Coal Calorific Value On Co? Emission Factors In Coal-Fired Power Plants: A Multi-Method Calculation Approach - Bayu Sukma; Gabriel Andari Kristanto (Riviera Publishing, 2025)
This study analyzed the carbon dioxide (CO?) emission factors of 27 coal-fired power plants in Indonesia using three different calculation approaches sourced from the scientific literature. This study aims to evaluate the accuracy and sensitivity of each method and examine the influence of the technical variables of the plant, namely boiler type and specification, unit capacity, and type of coal calories, on the value of specific CO? emission factors. Data were obtained from accredited emission verification institutions and analyzed in a quantitative descriptive manner with ANOVA statistical tests and correlation. The results showed that the energy output-based method (t CO?/MWh) was more representative of the actual generation conditions, with an average emission value of 1.18 t CO?/MWh. Units with supercritical technology and a capacity of >300 MW tended to have lower emission factors. In contrast, the use of low-calorie coal produces significantly higher emissions. This study provides important recommendations for direct calculation-based emission calculations, selection of low-emission technologies, and the formulation of low-carbon energy policies to support the achievement of Indonesia's NDC.